(untitled) (International Journal of Engineering Materials and Manufacture, 2023)
The effects of Cr and Ni on three different types of steel with different carbon ratios under constant conditions such as the welding current 120A, voltage 80V, Diameter 10 mm and angle 60 degree was observed. Nickel percentage of up to 0.147% and Chromium 0.083% contributed to affecting the mechanical properties of the steel. Undissolved carbide particles refine the austenite grain size. In the presence of nickel, chromium carbide is less effective in austenite grain refinement than chromium carbide in absence of nickel at temperature below 975°C. Nickel does not produce any austenite grain refinement but presence of nickel promotes the formation of acicular ferrites. It was also found that Ni and Cr as chromium carbide also refines the ferrite grain size and morphology. Cr as chromium carbide is more effective in refining ferrite grain size than nickel. The microstructure of the base metal as a reference material was analysed before heating to support the results of chemical analysis. Nickel percentage of up to 0.147% and Chromium 0.083%. Molybdenum was 0.03% which contributed to affecting the mechanical properties of the steel. Keyword: Alloy steel, Heat treatment, Chromium, Nickel, Grain size